STRATEGI CERDAS HUMAS PMI DALAM MENDORONG PARTISIPASI DONOR DARAH DI KABUPATEN JEMBER - Erdana, Rinata Lya; Susanti, Ari (Universitas Muhammadiyah Jember, 2024)
Abstract The Indonesian Red Cross (IRC), as a humanitarian organization, plays a vital role in ensuring the availability of blood supplies. Effective communication strategies by Public Relations are essential to fostering engagement with the community. This study aims to analyze the Public Relations strategies implemented by IRC to enhance awareness and encourage public participation in blood donation in Jember Regency, the communication channels utilized, and the challenges encountered in the process. The theory utilized in this research is the Cutlip, Center, and Broom Theory. Employing a qualitative approach, data collection methods include observation, interviews, and documentation. The research was conducted at the Blood Donor Unit of IRC Jember Regency, with informants selected through purposive sampling. The informants comprise IRC Public Relations officers, Blood Donor Unit Public Relations officers, the Head of the Blood Donor Unit, and the Head of the Administrative Division of the Blood Donor Unit in Jember Regency. The findings indicate that IRC’s Public Relations strategy in raising awareness and participation is executed through direct educational initiatives, social media campaigns, and collaborations with various institutions and community organizations. Programs such as mobile blood donation units, digital awareness campaigns, and strategic partnerships with hospitals constitute key efforts to enhance information dissemination. However, several obstacles remain, including limited public awareness, insufficient human resources, and misconceptions surrounding blood donation. This study concludes that while IRC Jember Regency’s communication strategies have been effective, further strengthening is required in promotional activities and sustained public engagement. Supporting factors include cross-sector collaboration, community involvement, and regulatory support, whereas inhibiting factors involve the lack of continuous education initiatives and low public participation in regular blood donations. Keywords: Public Relations Strategy, Blood Donation, Indonesian Red Cross